PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SEKOLAH DASAR - Nawang Anggi Rahmawati; Adelia Nur Thahira; Nurjannah; Destrinelli; Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students’ creativity and learning outcomes in Bahasa Indonesia subject through the implementation of the Project Based Learning (PjBL) model. This classroom action research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The subjects were 27 fourth-grade students at SDN 80/I Batanghari. Data collection techniques included observation, interviews, and documentation. The results showed an increase in both students’ creativity and learning outcomes. In Cycle I, the average creativity score was 61.1% and improved in Cycle II to 85%. The findings suggest that PjBL can effectively enhance students’ active participation and comprehension through project activities aligned with Bahasa Indonesia competencies.